Effect of early postoperative enteral nutrition on the short‐term prognosis in neonatal gastric perforation - Ting Zhu; Yu Liu; Huan Wei; Shuo Tang; Xiaowen Li; Mengying Cui; Yuan Shi; Zheng‐Li Wang (Pediatric Discovery)
Abstract The aim of this retrospective study was to investigate the impact of early postoperative enteral nutrition on the short‐term prognosis of neonatal gastric perforation. The 63 neonates were divided into two groups based on enteral nutrition timing: the early enteral nutrition (EEN) group (≤15 days) and the late enteral nutrition (LEN) group (>15 days). The EEN group was additionally matched with the LEN1 group based on closely aligned gestational age (difference ≤6 days), birth weight (difference <250 g), and age of onset (<1 day). Data from the EEN, LEN, and LEN1 groups were compared and analyzed. No significant differences were observed among the groups in baseline characteristics such as gestational age, birth weight, age at hospital admission, cesarean section rate, and so on (p > 0.05). Furthermore, preoperative comorbidities, clinical symptoms, and examination results were not significantly different between the three groups (p > 0.05). However, the time required to achieve total enteral nutrition, the length of hospital stay, and fistula retention time were significantly less in the EEN group compared to the LEN groups (p < 0.05). The EEN group also exhibited a shorter gastrointestinal decompression time than the LEN1 group, but other major postoperative outcome measures were not significantly different. In conclusion, our study suggests that early postoperative enteral nutrition (≤15 days) could reduce the time to total enteral nutrition, length of hospital stay, and fistula retention time, without increasing adverse prognosis rates.